Reagentless Quantum-Rate-Based Electrochemical Signal of Graphene for Detecting SARS-CoV-2 Infection Using Nasal Swab Specimens - Garrote, Beatriz Lucas [UNESP]; Lopes, Lais C. [UNESP]; Pinzon, Edgar F. [UNESP]; Mendonca-Natividade, Flavia C. [UNESP]; Martins, Ronaldo B.; Santos, Adriano [UNESP]; Arruda, Eurico; Bueno, Paulo R. [UNESP] (Amer Chemical Soc, 2022)
The quantum-rate model predicts a rate k as a frequency for transporting electrons within molecular structures, which is governed by the ratio between the quantum of conductance G and capacitance Cq, such that k = G/Cq. This frequency, as measured in a single-layer graphene appropriately modified with suitable biological receptors, can be applied as a transducer signal that ranges sensitivities within the attomole for biosensing applications. Here, we applied this label-free and reagentless biosensing transducer signal methodology for the qualitative diagnosis of COVID-19 infections, where this assay methodology was shown to be similar to the gold-standard real-time polymerase chain reaction. The quantum-rate strategy for the diagnosis of COVID-19 was performed by combining the response of the interface for detecting the S and N proteins of SARS-CoV-2 virus as accessed from nasopharyngeal/oropharyngeal patient samples with 80% of sensitivity and 77% of specificity. As a label-free and reagentless biosensing platform, the methodology is decidedly useful for point-of-care and internet-of-things biological assaying technologies, not only because of its real-time ability to measure infections but also because of the capability for miniaturization inherent in reagentless electrochemical methods. This approach effectively permits the rapid development of biological assays for surveillance and control of endemics and pandemics.
Keywords: Quantum rate; Electrochemical capacitance; Single-layer graphene; Label-free; Reagentless; Attomole sensitivity; Qualitative assay; SARS-CoV-2